The development of contemporary music culture of Tuva (a view from Japan) - Terada, Mao (The New Research of Tuva, 2017)
A philologist, graduate of Wako University (Tokyo), first heard Tuvan music in 1999 from a CD of a world-renowned band “Huun Huur Tu”. She started learning to perform xöömei. In 2000s she visited Tuva to participate in musical festivals, and in 2006 she decided to stay here to study music traditions. The musical life of Tuva does not stand still and steadily develops. In this article the author shares her personal observations and opinions on whether how and which direction does the contemporary Tuvan music evolve. There are a number of reasons for profound interest of the Japanese in Tuvan throat singing. Citizens of urbanized country, they feel the lack of “live” impressions, they are detached from the environment. Japan has almost no tale-tellers or ancient music instrument players left, reading sutras by Buddhist lamas became a very rare thing. Japanese compensate their sorrow for ancient sounds with the sounds of xöömei and Tuvan songs that express different moods and have a wide range of genres. The diversity of Tuvan musical instruments is amazing. The number of xöömei performers in Japan is constantly rising. Japanese xöömei performers invite Tuvan xöömeiji every year to Japan and visit Tuva within the cultural exchange programs. Tuvan musicians are in lasting creative pursuit. The music itself undergoes permanent versatile evolution. The author also takes interest in the best practices of women xöömei performers. Xöömei is being performed together with half-lost ancient melodies, the yet undiscovered variants of xöömei must be specific, as well. Performing xöömei in combination with modern forms of music-making significantly changes the context of xöömei’s functionality. Nonetheless, many young xöömeiji started rendering this unique art in more and more monotonous way. Every year we also see an increase in the number of foreign xöömei-performers.